2015
DOI: 10.19104/jhc.2014.102
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Visual Scoring of Coronary Artery Calcium (CAC) on Coronary Computed Tomography Angiogram (CCTA) to Agatston Score

Abstract: Purpose: Detection and quantification of coronary artery calcium (CAC) has a prognostic value for future cardiovascular events, beyond that accrued from other cardiovascular risk factors. CAC is conventionally measured as an Agatston score from an EKG-gated non-contrast CT of the heart using special software. The predominant indication for coronary CT angiography (CCTA) in clinical practice is to evaluate obstructive coronary artery disease (CAD) in a low to intermediate pretest probability population. At pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Since visual score does not require electrocardiogram (ECG) gating, the scoring can be done in any routine chest CT. visual score is a feasible method and correlates well with AS. Sonavane et al 21) showed a good correlation between visual score and AS with a good inter-reader correlation. Einstein et al 22) reported a high degree of association between visual score and AS on ungated low-dose CT scans used for attenuation correction on positron emission tomography/CT and single-photon emission CT/CT.…”
Section: Cac Scoring Techniquesmentioning
confidence: 94%
“…Since visual score does not require electrocardiogram (ECG) gating, the scoring can be done in any routine chest CT. visual score is a feasible method and correlates well with AS. Sonavane et al 21) showed a good correlation between visual score and AS with a good inter-reader correlation. Einstein et al 22) reported a high degree of association between visual score and AS on ungated low-dose CT scans used for attenuation correction on positron emission tomography/CT and single-photon emission CT/CT.…”
Section: Cac Scoring Techniquesmentioning
confidence: 94%